Assessment of comminution capacity related to molar intercuspation in catarrhines using a chewing simulator - Axelle EC Walker; Franck Guy; Christian Salles; Ghislain Thiery; Vincent Lazzari (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Mammalian molars play a central role during chewing, or food comminution, through cyclic dental occlusion. Mammals fragment food items with varying degrees of efficiency depending on their dental morphology, suggesting an adaptive link that is yet to be assessed. Here, we test the effect of molar morphology at maximum intercuspation (centric occlusion), i.e., between phases I and II, on the comminution of five food items that correspond to different mechanical challenges encountered by catarrhines. Using a chewing simulator, we experimentally measured the number of food fragments produced after five successive intercuspations with two different forces, in order to assess their influence. The sample includes cercopithecid and hominid specimens encompassing the main dental occlusal patterns and dietary habits displayed by extant and fossil catarrhines. We show that increasing bite force results in better food item degradation overall although we report some exceptions, notably for ductile and tough foods (apples, ginger and leaves). Brittle and complex foods (hazelnuts and crickets) are fragmented by intercuspation. This experiment showed that proper occlusion and bite force are sufficient only to fragment brittle food and that additional movements are necessary to fragment tough foods (leaves and grasses). It also highlights the masticatory capacities of various occlusal patterns in primates and our ability to test these with robotics, a breakthrough that will allow investigations of important anthropological questions concerning the evolution of dental morphology.